Acute right insular ischaemic lesions and poststroke left ventricular dysfunction - Winder, Klemens; Villegas Millar, Carolina; Siedler, Gabriela; Knott, Michael; Dörfler, Arnd; Engel, Anna; Achenbach, Stephan; Hilz, Max-Josef; Kallmünzer, Bernd; Schwab, Stefan; Seifert, Frank; Fröhlich, Kilian (Stroke and Vascular Neurology, 2023)
IntroductionMyocardial injury related to acute ischaemic stroke is common even without primary cardiac disease. We intended to determine associations between values of left ventricular ejection fraction (LVEF) and ischaemic stroke lesion sites. MethodsOf a local database, patients with acute first-ever ischaemic stroke confirmed by brain imaging but without pre-existing heart disease were included. The cardiac morphology and LVEF were obtained from transthoracic or transesophageal echocardiography, and impaired LVEF was categorised as mild (35%-50%), moderate (34%-25%) and severe (<25%). Patient age, stroke severity, ischaemic lesion volume, prevalence of troponin I increase (>0.1 ng/mL), atrial fibrillation and cardiac wall motion abnormalities were assessed and compared between patients with and without impaired LVEF after stroke (significance: p<0.05). A multivariate voxelwise lesion analysis correlated LVEF after stroke with sites of ischaemic lesions. ResultsOf 1209 patients who had a stroke, 231 (mean age 66.3 +/- 14.0 years) met the inclusion criteria; 40 patients (17.3%) had an impaired LVEF after stroke. Patients with impaired LVEF had higher infarct volumes (53.8 mL vs 30.0 mL, p=0.042), a higher prevalence of troponin increase (17.5% vs 4.2%, p=0.006), cardiac wall motion abnormalities (42.5% vs 5.2%, p<0.001) and atrial fibrillation (60.0% vs 26.2%, p<0.001) than patients with LVEF of >50%. The multivariate voxelwise lesion analysis yielded associations between decreased LVEF and damaged voxels in the insula, amygdala and operculum of the right hemisphere. ConclusionOur imaging analysis unveils a prominent role of the right hemispheric central autonomic network, especially of the insular cortex, in the brain-heart axis. Our results support preliminary evidence that acute ischaemic stroke in distinct brain regions of the central autonomic network may directly impair cardiac function and thus further supports the concept of a distinct stroke-heart syndrome.
CRIS-Team WoS Importer:2023-02-24

Age of epilepsy onset as modulating factor for naming deficit after epilepsy surgery: a voxel-based lesion-symptom mapping study - Reindl, Caroline; Walther, Katrin; Allgäuer, Anna-Lena; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Gollwitzer, Stephanie; Schwarz, Michael; Trollmann, Regina; Madzar, Dominik; Knott, Michael; Dörfler, Arnd; et al. (Scientific Reports, 2023)
Age at onset of epilepsy is an important predictor of deterioration in naming ability following epilepsy surgery. In 141 patients with left hemispheric epilepsy and language dominance who received epilepsy surgery at the Epilepsy Centre Erlangen, naming of objects (Boston naming test, BNT) was assessed preoperatively and 6 months postoperatively. Surgical lesions were plotted on postoperative MRI and normalized for statistical analysis using voxel-based lesion-symptom mapping (VBLSM). The correlation between lesion and presence of postoperative naming deterioration was examined varying the considered age range of epilepsy onsets. The VBLSM analysis showed that volumes of cortex areas in the left temporal lobe, which were associated with postoperative decline of naming, increased with each year of later epilepsy onset. In patients with later onset, an increasing left posterior temporobasal area was significantly associated with a postoperative deficit when included in the resection. For late epilepsy onset, the temporomesial expansion also included the left hippocampus. The results underline that early onset of epilepsy is a good prognostic factor for unchanged postoperative naming ability following epilepsy surgery. For later age of epilepsy onset, the extent of the area at risk of postoperative naming deficit at 6 months after surgery included an increasing left temporobasal area which finally also comprised the hippocampus.
CRIS-Team Scopus Importer:2023-09-08

Can flat-detector CT after successful endovascular treatment predict long-term outcome in patients with large vessel occlusion? An Alberta Stroke Programme Early CT Score–based study - Knott, Michael; Hölter, Philip; Hock, Stefan; Mühlen, Iris; Gerner, Stefan; Sprügel, Maximilian; Huttner, Hagen; Schwab, Stefan; Engelhorn, Tobias; Dörfler, Arnd (Neurological Sciences, 2022)
Purpose: Recent studies postulate a high prognostic value of the Alberta Stroke Programme Early CT Score (ASPECTS) applied on non-contrast whole-brain flat-detector CT (FDCT) after successful endovascular treatment (EVT). The aim of this study was the evaluation of long-term patient outcome after endovascular treatment using postinterventional FDCT. Methods: Using a local database (Stroke Research Consortium in Northern Bavaria, STAMINA), 517 patients with successful endovascular treatment (modified Thrombolysis in Cerebral Infarction (mTICI) ≥ 2B) due to acute ischaemic stroke (AIS) and large vessel occlusion (LVO) of the anterior circulation were recruited retrospectively. In all cases, non-contrast FDCT after EVT was analysed with special focus at ASPECTS. These results were correlated with the functional outcome in long-term (modified Rankin Scale (mRS) shift from pre-stroke to 90 days after discharge). Results: A significant difference in FDCT-ASPECTS compared to the subgroup of favourable vs. unfavourable outcome (Δ mRS) (median ASPECTS 10 (10–9) vs. median ASPECTS 9 (10–7); p = 0,001) could be demonstrated. Multivariable regression analysis revealed FDCT-ASPECTS (OR 0.234, 95% CI − 0.102–0.008, p = 0.022) along with the NHISS at admission (OR 0.169, 95% CI 0.003–0.018, p = 0.008) as independent factors for a favourable outcome. Cut-off point for a favourable outcome (Δ mRS) was identified at an ASPECTS ≥ 8 (sensitivity 90.6%, specificity 35%). Conclusion: For patients with LVO and successful EVT, FDCT-ASPECTS was found to be highly reliable in predicting long-term outcome.
CRIS-Team Scopus Importer:2022-12-02
Keywords: ASPECTS; Endovascular treatment; Flat-detector CT; Stroke

Can Perfusion-Based Brain Tissue Oxygenation MRI Support the Understanding of Cerebral Abscesses In Vivo? - Knott, Michael; Hölter, Philip; Soder, Liam; Schlaffer, Sven-Martin; Hoffmanns, Sophia; Lang, Roland; Dörfler, Arnd; Schmidt, Manuel (Diagnostics, 2023)
Purpose: The clinical condition of a brain abscess is a potentially life-threatening disease. The combination of MRI-based imaging, surgical therapy and microbiological analysis is critical for the treatment and convalescence of the individual patient. The aim of this study was to evaluate brain tissue oxygenation measured with dynamic susceptibility contrast perfusion weighted imaging (DSC-PWI) in patients with brain abscess and its potential benefit for a better understanding of the environment in and around brain abscesses. Methods: Using a local database, 34 patients (with 45 abscesses) with brain abscesses treated between January 2013 and March 2021 were retrospectively included in this study. DSC-PWI imaging and microbiological work-up were key inclusion criteria. These data were analysed regarding a correlation between DSC-PWI and microbiological result by quantifying brain tissue oxygenation in the abscess itself, the abscess capsula and the surrounding oedema and by using six different parameters (CBF, CBV, CMRO2, COV, CTH and OEF). Results: Relative cerebral blood flow (0.335 [0.18–0.613] vs. 0.81 [0.49–1.08], p = 0.015), relative cerebral blood volume (0.44 [0.203–0.72] vs. 0.87 [0.67–1.2], p = 0.018) and regional cerebral metabolic rate for oxygen (0.37 [0.208–0.695] vs. 0.82 [0.55–1.19], p = 0.022) were significantly lower in the oedema around abscesses without microbiological evidence of a specific bacteria in comparison with microbiological positive lesions. Conclusions: The results of this study indicate a relationship between brain tissue oxygenation status in DSC-PWI and microbiological/inflammatory status. These results may help to better understand the in vivo environment of brain abscesses and support future therapeutic decisions.
CRIS-Team Scopus Importer:2023-11-24
Keywords: brain abscess; brain tissue oxygenation; DSC-PWI

Cerebral lesions sites in neurosarcoidosis: a lesion mapping study - Fröhlich, Kilian; Mrochen, Anne; Wang, Ruihao; Haupenthal, David; Macha, Kosmas; Siedler, Gabriela; Knott, Michael; Dörfler, Arnd; Schwab, Stefan; Winder, Klemens (Journal of Neurology, 2023)
Background and purpose: Sarcoidosis is a granulomatous disease of unknown etiology affecting the central nervous system in up to 15% of the patients. Diagnosis of neurosarcoidosis is very challenging due to the heterogeneity of its clinical manifestation. This study intended to evaluate the distribution of cerebral lesion sites and the potential presence of specific lesion clusters in neurosarcoidosis patients using voxel-based lesion symptom mapping (VLSM). Methods: Patients with neurosarcoidosis were retrospectively identified and included between 2011 and 2022. Cerebral lesion sites were correlated voxel-wise with presence and absence of neurosarcoidosis using non-parametric permutation test. Multiple sclerosis patients served as controls for the VLSM-analysis. Results: Thirty-four patients (mean age 52 ± 15 years) of whom 13 were diagnosed with possible, 19 with probable and 2 with confirmed neurosarcoidosis were identified. Lesion overlap of neurosarcoidosis patients demonstrated a distribution of white matter lesions in all brain areas, with a periventricular predilection similar to multiple sclerosis. In contrast to multiple sclerosis controls, no propensity for lesions in proximity of the corpus callosum was observed. Neurosarcoidosis lesions appeared smaller and lesion volume was lower in the neurosarcoidosis cohort. The VLSM analysis showed minor associations between neurosarcoidosis and damaged voxels in the bilateral frontobasal cortex. Conclusions: The VLSM analysis yielded significant associations in the bilateral frontal cortex, suggesting that leptomeningeal inflammatory disease with following cortical involvement is a quite specific feature in neurosarcoidosis. Lesion load was lower in neurosarcoidosis than in multiple sclerosis. However, no specific pattern of subcortical white matter lesions in neurosarcoidosis was revealed.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Cerebral lesions; Neurosarcoidosis; Sarcoidosis; Voxel-based lesion symptom mapping

CEREBROSPINAL FLUID BIOMARKERS FOR CEREBRAL AMYLOID ANGIOPATHY - Sembill, Jochen; Lusse, C.; Linnerbauer, Mathias; Sprügel, Maximilian; Mrochen, Anne; Knott, Michael; Hölter, Philip; Engelhorn, Tobias; Schmidt, M.; Dörfler, Arnd; Oberstein, Timo; Maler, Juan Manuel; et al. (INTERNATIONAL JOURNAL OF STROKE, 2022)
CRIS-Team WoS Importer:2022-11-18

Cerebrospinal fluid biomarkers for cerebral amyloid angiopathy - Sembill, Jochen; Lusse, Christoph; Linnerbauer, Mathias; Sprügel, Maximilian; Mrochen, Anne; Knott, Michael; Engelhorn, Tobias; Schmidt, Manuel; Dörfler, Arnd; Oberstein, Timo; Maler, Juan Manuel; Kornhuber, Johannes; et al. (Brain Communications, 2023)
Integrating cerebrospinal fluid-biomarkers into diagnostic workup of patients with sporadic cerebral amyloid angiopathy may support early and correct identification. We aimed to identify and validate clinical- and cerebrospinal fluid-biomarkers for in vivo diagnosis of cerebral amyloid angiopathy. This observational cohort study screened 2795 consecutive patients admitted for cognitive complaints to the academic departments of neurology and psychiatry over a 10-year period (2009–2018). We included 372 patients with available hemosiderin-sensitive MR imaging and cerebrospinal fluid-based neurochemical dementia diagnostics, i.e. Aβ40, Aβ42, t-tau, p-tau. We investigated the association of clinical- and cerebrospinal fluid-biomarkers with the MRI-based diagnosis of cerebral amyloid angiopathy, applying confounder-adjusted modelling, receiver operating characteristic and unsupervised cluster analyses. We identified 67 patients with cerebral amyloid angiopathy, 76 patients with Alzheimer’s disease, 75 patients with mild cognitive impairment due to Alzheimer’s disease, 76 patients with mild cognitive impairment with unlikely Alzheimer’s disease and 78 healthy controls. Patients with cerebral amyloid angiopathy showed a specific cerebrospinal fluid pattern: average concentration of Aß40 [13 792 pg/ml (10 081–18 063)] was decreased compared to all controls (P < 0.05); Aß42 [634 pg/ml (492–834)] was comparable to Alzheimer’s disease and mild cognitive impairment due to Alzheimer’s disease (P = 0.10, P = 0.93) but decreased compared to mild cognitive impairment and healthy controls (both P < 0.001); p-tau [67.3 pg/ml (42.9–91.9)] and t-tau [468 pg/ml (275–698)] were decreased compared to Alzheimer’s disease (P < 0.001, P = 0.001) and mild cognitive impairment due to Alzheimer’s disease (P = 0.001, P = 0.07), but elevated compared to mild cognitive impairment and healthy controls (both P < 0.001). Multivariate modelling validated independent clinical association of cerebral amyloid angiopathy with older age [odds-ratio: 1.06, 95% confidence interval (1.02–1.10), P < 0.01], prior lobar intracerebral haemorrhage [14.00 (2.64–74.19), P < 0.01], prior ischaemic stroke [3.36 (1.58–7.11), P < 0.01], transient focal neurologic episodes (TFNEs) [4.19 (1.06–16.64), P = 0.04] and gait disturbance [2.82 (1.11–7.15), P = 0.03]. For cerebrospinal fluid-biomarkers per 1 pg/ml, both lower Aß40 [0.9999 (0.9998–1.0000), P < 0.01] and lower Aß42 levels [0.9989 (0.9980–0.9998), P = 0.01] provided an independent association with cerebral amyloid angiopathy controlled for all aforementioned clinical confounders. Both amyloid biomarkers showed good discrimination for diagnosis of cerebral amyloid angiopathy among adjusted receiver operating characteristic analyses (area under the receiver operating characteristic curves, Aß40: 0.80 (0.73–0.86), P < 0.001; Aß42: 0.81 (0.75–0.88), P < 0.001). Unsupervised Euclidian clustering of all cerebrospinal fluid-biomarker-profiles resulted in distinct segregation of cerebral amyloid angiopathy patients from all controls. Together, we demonstrate that a distinctive set of cerebrospinal fluid-biomarkers effectively differentiate cerebral amyloid angiopathy patients from patients with Alzheimer’s disease, mild cognitive impairment with or without underlying Alzheimer’s disease, and healthy controls. Integrating our findings into a multiparametric approach may facilitate diagnosing cerebral amyloid angiopathy, and may aid clinical decision-making, but warrants future prospective validation.
CRIS-Team Scopus Importer:2023-07-21
Keywords: biomarker; cerebral amyloid angiopathy; cerebrospinal fluid; dementia; small vessel disease

Comparison of Two Automated Computed Tomography Perfusion Applications to Predict the Final Infarct Volume After Thrombolysis in Cerebral Infarction 3 Recanalization - Mühlen, Iris; Sprügel, Maximilian; Hölter, Philip; Hock, Stefan; Knott, Michael; Huttner, Hagen; Schwab, Stefan; Kallmünzer, Bernd; Dörfler, Arnd (Stroke, 2022)
Background: Several automated computed tomography perfusion software applications have been developed to provide support in the definition of ischemic core and penumbra in acute ischemic stroke. However, the degree of interchangeability between software packages is not yet clear. Our study aimed to evaluate 2 commonly used automated perfusion software applications (Syngo.via and RAPID) for the indication of ischemic core with respect to the follow-up infarct volume (FIV) after successful recanalization and with consideration of the clinical impact. Methods: Retrospectively, 154 patients with large vessel occlusion of the middle cerebral artery or the internal carotid artery, who underwent endovascular therapy with a consequent Thrombolysis in Cerebral Infarction 3 result within 2 hours after computed tomography perfusion, were included. Computed tomography perfusion core volumes were assessed with both software applications with different thresholds for relative cerebral blood flow (rCBF). The results were compared with the FIV on computed tomography within 24 to 36 hours after recanalization. Bland-Altman was applied to display the levels of agreement and to evaluate systematic differences. Results: Highest correlation between ischemic core volume and FIV without significant differences was found at a threshold of rCBF<38% for the RAPID software (r=0.89, P<0.001) and rCBF<25% for the Syngo software (r=0.87, P<0.001). Bland-Altman analysis revealed best agreement in these settings. In the vendor default settings (rCBF<30% for RAPID and rCBF<20% for Syngo) correlation between ischemic core volume and FIV was also high (RAPID: r=0.88, Syngo: r=0.86, P<0.001), but mean differences were significant (P<0.001). The risk of critical overestimation of the FIV was higher with rCBF<38% (RAPID) and rCBF<25% (Syngo) than in the default settings. Conclusions: By adjusting the rCBF thresholds, comparable results with reliable information on the FIV after complete recanalization can be obtained both with the RAPID and Syngo software. Keeping the software specific default settings means being more inclusive in patient selection, but forgo the highest possible accuracy in the estimation of the FIV.
CRIS-Team WoS Importer:2022-05-13

Diagnostic Performance of 0.55 T MRI for Intracranial Aneurysm Detection - Osmanodja, Filiz; Rösch, Julie; Knott, Michael; Dörfler, Arnd; Grodzki, David; Uder, Michael; Heiß, Rafael (Investigative Radiology, 2023)
OBJECTIVES: Intracranial aneurysm (IA) is the main cause of subarachnoid hemorrhages. Time-of-flight (TOF) magnetic resonance angiography (MRA) at 1.5 T or 3 T magnetic resonance imaging (MRI) is a well-established method for the diagnosis of IA. The aim of this prospective study was to evaluate the performance of a modern 0.55 T MRI in the diagnosis of IAs in comparison to digital subtraction angiography (DSA) as a standard of reference. MATERIALS AND METHODS: Seventeen patients with suspicion of single or multiple IAs underwent TOF MRA at 0.55 T MRI 1 day before DSA. Two neuroradiologists independently measured the aneurysm neck, width, and height on 0.55 T, 1.5 T, and 3 T 3D-TOF MRA source images and 2D/3D rotational angiography. The main analysis assessed the intermodality agreement between 0.55 T TOF MRA and DSA using Bland-Altman plots, a Wilcoxon test, and the intraclass correlation coefficient (ICC). In a secondary analysis, aneurysm dimensions were compared between 0.55 T TOF MRA and 1.5/3 T TOF MRA. Interreader agreement was evaluated by ICC. A third neuroradiologist blinded to patient history screened 0.55 T TOF MRA data sets of the aforementioned 17 patients and 15 additional healthy patients for the presence and location of aneurysms. RESULTS: A total of 19 aneurysms in 16 patients were identified in both 0.55 T MRA and DSA. Measurements of the 2 nonblinded readers showed no significant differences between 0.55 T TOF MRA and DSA in the overall aneurysm size (calculated as the mean from height/width/neck) ( P = 0.178), as well as in the mean width ( P = 0.778) and neck values ( P = 0.190). The mean height was significantly larger in 0.55 T TOF MRA in comparison to DSA ( P = 0.020). Intermodality (1.5/3 T TOF MRA) and interrater agreement were excellent (ICC > 0.94). Of the 32 data sets of patients with and without IA, the blinded reader detected all aneurysms correctly by using 0.55 T images. CONCLUSIONS: TOF-MRA acquired with a modern 0.55 T MRI is a reliable tool for the detection and initial assessment of IAs.
CRIS-Team Scopus Importer:2023-01-20

Endovascular thrombectomy in patients with anterior circulation stroke: an emulated real-world comparison - Sembill, Jochen; Sprügel, Maximilian; Haupenthal, David; Kremer, Svenja; Knott, Michael; Mühlen, Iris; Kallmünzer, Bernd; Kuramatsu, Joji (Neurological Research and Practice, 2024)
Background: Endovascular thrombectomy (EVT) has been proven effective in anterior circulation stroke due to large vessel occlusion (LVO). However, translation from randomized clinical trials (RCTs) with highly selected patients to real-world requires confirmation, particularly to identify associations outside of strict selection criteria. Aims: This study aims to compare functional outcomes after EVT in real-world with those reported in RCTs, and to identify associations with functional outcome after EVT outside RCT-criteria. Methods: This study analyzed longitudinal German real-world data from the Stroke Research Consortium in Northern Bavaria (STAMINA) cohort from January, 2015 to June, 2019. We conducted a trial emulation, comparing patients with anterior circulation stroke and LVO meeting selection criteria for RCTs investigating EVT (1) predominantly within 6 hours with those from HERMES meta-analysis, and (2) within 6-24 hours with those from AURORA meta-analysis. We (3) analyzed treatment effects of EVT and association with functional outcome in patients treated outside RCT criteria. Results: Of 598 patients, 281 (47.0%) met RCT-criteria for treatment within 6 hours (hereinafter STAMINA-HERMES), 74 (12.4%) met RCT-criteria for treatment within 6–24 hours (STAMINA-AURORA), and 277 (46.3%) patients received EVT outside RCT-criteria. We observed no difference in rates of functional independence or mortality, comparing STAMINA-HERMES with HERMES meta-analysis (mRS 0-1: n=120/281 [43%] vs. 291/633 [46%], p=0.36; mortality: n=34/281 [12%] vs. 97/633 [15%], p=0.20), and STAMINA-AURORA with AURORA meta-analysis (mRS 0-1: n=26/74 [35%] vs. 122/266 [46%], p=0.10, mortality: n=10/74 [14%] vs. 45/266 [17%], p=0.48). Patients treated outside RCT-criteria had worse outcome (mRS 0-1: n=38/277 [14%], mortality: n=90/277 [32%], both p<0.001); possibly driven by pre-existing functional dependence (n=172/277 [62%]). Compared to matched controls, EVT outside of RCT-criteria was associated with lower mortality (absolute treatment effect: -14%, 95% Confidence Interval [CI] -23 to -5, p<0.01), but not with recovery to functional independence or premorbid functional status (treatment effect: 4%, CI -4 to 11, p=0.34), which was associated with lower NIHSS (Odds ratio [OR] 0.86, CI 0.80-0.92, p<0.001) and age (OR 0.95, CI 0.93-0.98, p=0.002). Conclusions: Translation of EVT outcomes reported in RCTs into real-world is possible, however, almost half of patients did not meet trial criteria. Identification of patients who functionally benefit from frequently performed EVT outside RCT-criteria requires further investigation. Trial registration: Clinicaltrials.gov, NCT04357899.
CRIS-Team Scopus Importer:2024-08-02
Keywords: Stroke; Thrombectomy; Treatment

Evaluation of Functional Recovery Following Thrombectomy in Patients With Large Vessel Occlusion and Prestroke Disability - Sprügel, Maximilian; Sembill, Jochen; Kremer, Svenja; Gerner, Stefan; Knott, Michael; Hock, Stefan; Engelhorn, Tobias; Dörfler, Arnd; Huttner, Hagen; Schwab, Stefan (JAMA Network Open, 2022)
IMPORTANCE It is uncertain whether thrombectomy is associated with benefits in patients with prestroke disability.
CRIS-Team WoS Importer:2022-09-02

Incidence, temporal profile and neuroanatomic correlates of poststroke epilepsy - Winder, Klemens; Bobinger, Tobias; Seifert, Frank; Mrochen, Anne; Haupenthal, David; Knott, Michael; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Fröhlich, Kilian (Journal of Neuroimaging, 2023)
Background and Purpose: The relationship between ischemic stroke site and occurrence of poststroke epilepsy (PSE) is incompletely understood. This study intended to evaluate incidence and temporal profiles of seizures and to correlate ischemic lesion sites with PSE using voxel-based lesion symptom mapping (VLSM). Methods: Patients with imaging-confirmed first-ever ischemic stroke without prior history of epilepsy were prospectively included. Demographic data, cardiovascular risk factors, and National Institute of Health Stroke Scale (NIHSS) scores were assessed. Data on seizures and modified Rankin scale scores were determined within a 90-day period after stroke onset. Ischemic lesion sites were correlated voxel wise with occurrence of PSE using nonparametric permutation test. Age- and sex-matched patients with first-ever ischemic strokes without PSE after 90 days served as controls for the VLSM analysis. Results: The stroke database contained 809 patients (mean age: 68.4 ± 14.2 years) with first-ever imaging-confirmed ischemic strokes without history of epilep. Incidence of PSE after 90-day follow-up was 2.8%. Five additional patients were admitted to the emergency department with a seizure after 90-day follow-up. Fifty percent of the seizures occurred in the acute phase after stroke. PSE patients had higher NIHSS scores and infarct volumes compared to controls without PSE (p <.05). PSE patients had infarcts predominantly involving the cerebral cortex. The hemisphere-specific VLSM analysis shows associations between PSE and damaged voxels in the left-hemispheric temporo-occipital transition zone. Conclusions: The data indicate that PSE occurs in a small proportion of patients with rather large ischemic strokes predominantly involving the cerebral cortex. Especially patients with ischemic lesions in the temporo-occipital cortex are vulnerable to develop PSE.
CRIS-Team Scopus Importer:2023-05-19
Keywords: ischemic stroke; poststroke epilepsy; voxel-based lesion symptom mapping

Microcatheters with extra-long detachable tip: A promising treatment option in dural arteriovenous fistulas - Gölitz, Philipp; Lücking, Hannes; Knott, Michael; Hock, Stefan; Brandner, Sebastian; Knossalla, Frauke; Dörfler, Arnd (Interventional Neuroradiology, 2022)
Purpose Treating cerebral dural arteriovenous fistulas (dAVFs) by transarterial embolization is an established endovascular approach but no data exist regarding the utility of using the newly introduced microcatheters with extra-long detachable tip. Aim of our study was to evaluate the value of these microcatheters and, additionally, of combining them with the simplified pressure cooker technique. Methods Twenty-nine patients treated for dAVF with transarterial embolization were enrolled. In a subgroup of fifteen patients the simplified pressure cooker technique was additionally applied. Demographics and characteristics were collected for patients and dAVFs and procedural details reviewed. The association between covariates and binary-coded occlusion status was evaluated. Results Microcatheter navigation into the target pedicle as well as application of the simplified pressure cooker technique were successful in all cases. Complete dAVF occlusion was reached in 69.0% at a single stage. In case of complete dAVF occlusion, embolization via only one pedicle was enough. Subgroup analysis revealed a higher occlusion status (80%) if using the simplified pressure cooker technique than if not (57%) but reached not significance level. Conclusion Using microcatheters with extra-long detachable tip for dAVF embolization seems to offer a safe and effective treatment option with exceptional high occlusion rate at a single stage. The high navigability facilitates catheterization of a single selected target pedicle that is often enough to reach complete dAVF occlusion. Combining these microcatheters with the simplified pressure cooker technique turned out to be safe and easy to handle and might allow an increasing dAVF occlusion rate.
CRIS-Team WoS Importer:2022-10-14

Prognostic Accuracy of CTP Summary Maps in Patients with Large Vessel Occlusive Stroke and Poor Revascularization after Mechanical Thrombectomy-Comparison of Three Automated Perfusion Software Applications - Mühlen, Iris; Borutta, Matthias; Siedler, Gabriela; Engelhorn, Tobias; Hock, Stefan; Knott, Michael; Hölter, Philip; Volbers, Bastian; Schwab, Stefan; Dörfler, Arnd (Tomography, 2022)
Background: Innovative automated perfusion software solutions offer support in the management of acute stroke by providing information about the infarct core and penumbra. While the performance of different software solutions has mainly been investigated in patients with successful recanalization, the prognostic accuracy of the hypoperfusion maps in cases of futile recanalization has hardly been validated. Methods: In 39 patients with acute ischemic stroke (AIS) due to large vessel occlusion (LVO) in the anterior circulation and poor revascularization (thrombolysis in cerebral infarction (TICI) 0-2a) after mechanical thrombectomy (MT), hypoperfusion analysis was performed using three different automated perfusion software solutions (A: RAPID, B: Brainomix e-CTP, C: Syngo.via). The hypoperfusion volumes (HV) as Tmax > 6 s were compared with the final infarct volumes (FIV) on follow-up CT 36-48 h after futile recanalization. Bland-Altman analysis was applied to display the levels of agreement and to evaluate systematic differences. Based on the median hypoperfusion intensity ratio (HIR, volumetric ratio of tissue with a Tmax > 10 s and Tmax > 6 s) patients were dichotomized into high- and low-HIR groups. Subgroup analysis with favorable (<0.6) and unfavorable (>= 0.6) HIR was performed with respect to the FIV. HIR was correlated to clinical baseline and outcome parameters using Pearson's correlation. Results: Overall, there was good correlation without significant differences between the HVs and the FIVs with package A (r = 0.78, p < 0.001) being slightly superior to B and C. However, levels of agreement were very wide for all software applications in Bland-Altman analysis. In cases of large infarcts exceeding 150 mL the performance of the automated software solutions generally decreased. Subgroup analysis revealed the FIV to be generally underestimated in patients with HIR >= 0.6 (p < 0.05). In the subgroup with favorable HIR, however, there was a trend towards an overestimation of the FIV. Nevertheless, packages A and B showed good correlation between the HVs and FIVs without significant differences (p > 0.2), while only package C significantly overestimated the FIV (-54.6 +/- 56.0 mL, p = 0.001). The rate of modified Rankin Scale (mRS) 0-3 after 3 months was significantly higher in favorable vs. unfavorable HIR (42.1% vs. 13.3%, p = 0.02). Lower HIR was associated with higher Alberta Stroke Program Early CT Score (ASPECTS) at presentation and on follow-up imaging, lower risk of malignant edema, and better outcome (p < 0.05). Conclusion: Overall, the performance of the automated perfusion software solutions to predict the FIV after futile recanalization is good, with decreasing accuracy in large infarcts exceeding 150 mL. However, depending on the HIR, FIV can be significantly over- and underestimated, with Syngo showing the widest range. Our results indicate that the HIR can serve as valuable parameter for outcome predictions and facilitate the decision whether or not to perform MT in delicate cases.
CRIS-Team WoS Importer:2022-07-08

Pulsed Arterial Spin Labeling and Segmented Brain Volumetry in the Diagnostic Evaluation of Frontotemporal Dementia, Alzheimer’s Disease and Mild Cognitive Impairment - Marterstock, Dominique; Knott, Michael; Lang, Stefan; Oberstein, Timo; Kornhuber, Johannes; Dörfler, Arnd; Schmidt, Manuel; Hölter, Philip (Tomography, 2022)
Background: Previous studies suggest that brain atrophy can not only be defined by its morphological extent, but also by the cerebral blood flow (CBF) within a certain area of the brain, including white and gray matter. The aim of this study is to investigate known atrophy patterns in different forms of dementia and to compare segmented brain volumetrics and pulsed arterial spin labeling (pASL) data to explore the correlation between brain maps with atrophy and this non-contrast-enhanced brain-perfusion method. Methods: Our study comprised 17 patients with diagnosed cognitive impairment (five Alzheimer’s disease = AD, five frontotemporal dementia = FTD, seven mild cognitive impairment = MCI) and 19 healthy control subjects (CO). All patients and controls underwent 4D-pASL brain-perfusion MR imaging and T1w MPRAGE. The data were assessed regarding relative brain volume on the basis of 286 brain regions, and absolute and relative cerebral blood flow (CBF/rCBF) were derived from pASL data in the corresponding brain regions. Mini-Mental State Examination (MMSE) was performed to assess cognitive functions. Results: FTD patients demonstrated significant brain atrophy in 43 brain regions compared to CO. Patients with MCI showed significant brain atrophy in 18 brain regions compared to CO, whereas AD patients only showed six brain regions with significant brain atrophy compared to CO. There was good correlation of brain atrophy and pASL perfusion data in five brain regions of patients with diagnosed FTD, especially in the superior temporal gyrus (r = 0.900, p = 0.037), the inferior frontal white matter (pars orbitalis; r = 0.968, p = 0.007) and the thalami (r = 0.810, p = 0.015). Patients with MCI demonstrated a correlation in one brain region (left inferior fronto-occipital fasciculus; r = 0.786, p = 0.036), whereas patients with diagnosed AD revealed no correlation. Conclusions: pASL can detect affected brain regions in cognitive impairment and corresponds with brain atrophy, especially for patients suffering from FTD and MCI. However, there was no correlation of perfusion alterations and brain atrophy in AD. pASL perfusion might thus represent a promising tool for noninvasive brain-perfusion evaluation in specific dementia subtypes as a complimentary imaging-based bio marker in addition to brain volumetry.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Alzheimer’s disease; Brain volumetry; Dementia; Frontotemporal dementia; Mild cognitive impairment; Pulsed arterial spin labeling

Simplified Edinburgh CT Criteria for Identification of Lobar Intracerebral Hemorrhage Associated With Cerebral Amyloid Angiopathy - Sembill, Jochen; Knott, Michael; Xu, Mingming; Röder, Sebastian; Hagen, Manuel; Sprügel, Maximilian; Mrochen, Anne; Borutta, Matthias; Hölter, Philip; Engelhorn, Tobias Martin; Rothhammer, Veit; Macha, Kosmas; et al. (Neurology, 2022)
BACKGROUND AND OBJECTIVES: In patients with lobar intracerebral hemorrhage (ICH), etiologic characterization represents a tradeoff between feasibility, resource allocation, and diagnostic certainty. This study investigated the accuracy and clinical utility of the simplified Edinburgh CT criteria to identify underlying cerebral amyloid angiopathy (CAA). METHODS: This external validation analyzed 210 consecutive patients with lobar ICH and available CT and MRI studies from a prospective single-center observational cohort study (2006-2015, Longitudinal Cohort Study on ICH Care [UKER-ICH,] NCT03183167). We investigated the interrater variability and diagnostic accuracy of the simplified Edinburgh CT-based criteria for identification of ICH associated with probable CAA according to MRI-based modified Boston criteria as a reference standard. We evaluated the utility of the simplified Edinburgh criteria by decision curve analysis, comparing the theoretical clinical net benefit (weighted benefit-harm at varying threshold probabilities) of the high-risk category (finger-like projections and subarachnoid hemorrhage) for ruling in and the low-risk category (neither finger-like projections nor subarachnoid hemorrhage) for ruling out with the assumptions of no or all patients having CAA (default strategies). RESULTS: Of 210 patients, 70 (33.3%) had high risk, 67 (31.9%) had medium risk, and 73 (34.8%) had low risk for CAA-associated ICH according to simplified Edinburgh CT criteria, showing moderate interrater variability. Discrimination was good (area under the receiver operating characteristics curve 0.74, 95% CI 0.67-0.81) without evidence of poor calibration (Hosmer-Lemeshow, p = 0.54) for validation of MRI-based diagnosis of probable CAA (n = 94 of 210, 44.8%). The rule-in criteria (high risk), had 87.1% (79.3%-92.3%) specificity, and the rule-out criteria (low risk), had 80.9% (71.1%-88.0%) sensitivity. Decision curve analysis suggested a theoretical clinical net benefit for ruling in but not for ruling out probable CAA compared to default strategies. DISCUSSION: Applying the simplified Edinburgh CT criteria during diagnostic workup seems clinically useful and may accurately identify CAA in patients with lobar ICH. TRIAL REGISTRATION INFORMATION: ClinicalTrials.gov Identifier: NCT03183167. CLASSIFICATION OF EVIDENCE: This study provides Class II evidence that in patients with lobar hemorrhages, the simplified Edinburgh criteria accurately identify those at high risk of CAA.
CRIS-Team Scopus Importer:2022-06-03

Voxel-wise lesion mapping of restless legs syndrome in multiple sclerosis - Fröhlich, Kilian; Knott, Michael; Hock, Stefan; Dörfler, Arnd; Seifert, Frank; Winder, Klemens (Neurological Sciences, 2022)
Objective Restless legs syndrome (RLS) is known to be associated with multiple sclerosis (MS) and may be caused by MS lesions in specific cerebral brain regions. Applying a voxel-wise lesion analysis, we tried to identify the contribution of cerebral MS lesions to RLS. Methods In this retrospective study, we established a cohort of people with MS with documented RLS and controls of people with MS without RLS matched disease severity. Diagnosis of MS and RLS was based on the current guidelines. The MS lesions were analyzed on T2-weighted magnetic resonance imaging scans (1.5 or 3 T). After manual delineation, lesion maps were converted into stereotaxic space. We generated a lesion overlap and performed a Liebermeister test with 4000 permutations to compare the absence or presence of RLS voxel-wise between patients with and without lesions in a given voxel. Results Forty of the patients with RLS and MS fulfilled the inclusion criteria. The voxel-wise analysis yielded associations between RLS and MS in the subcortex of the left gyrus precentralis. Conclusion Our voxel-wise analysis shows associations in the subcortex of the left gyrus precentralis. Thus, our data suggests that a dysfunction of the efferent motor system due to cerebral lesions may contribute to the pathophysiology of RLS in MS.
CRIS-Team WoS Importer:2022-05-20

Why Does It Shine?-A Prognostic Analysis about Predisposing Factors for Blood-Brain Barrier Damage after Revascularisation of Cerebral Large-Vessel Occlusion. - Knott, Michael; Hock, Stefan; Soder, Liam; Mühlen, Iris; Kremer, Svenja; Sprügel, Maximilian; Sembill, Jochen; Kuramatsu, Joji; Schwab, Stefan; Engelhorn, Tobias; Dörfler, Arnd (Journal of Cardiovascular Development and Disease, 2023)
BACKGROUND: Hyperdense lesions in CT after EVT of LVO are common. These lesions are predictors for haemorrhages and an equivalent of the final infarct. The aim of this study based on FDCT was the evaluation of predisposing factors for these lesions. METHODS: Using a local database, 474 patients with mTICI ≥ 2B after EVT were recruited retrospectively. A postinterventional FDCT after recanalisation was analysed regarding such hyperdense lesions. This was correlated with a variety of items (demographics, past medical history, stroke assessment/treatment and short-/long-term follow-up). RESULTS: Significant differences were present in NHISS at admission, regarding time window, ASPECTS in initial NECT, location of the LVO, CT-perfusion (penumbra, mismatch ratio), haemostatic parameters (INR, aPTT), duration of EVT, number of EVT attempts, TICI, affected brain region, volume of demarcation and FDCT-ASPECTS. The ICH-rate, the volume of demarcation in follow-up NECT and the mRS at 90 days differed in association with these hyperdensities. INR, the location of demarcation, the volume of demarcation and the FDCT-ASPECTS could be demonstrated as independent factors for the development of such lesions. CONCLUSION: Our results support the prognostic value of hyperdense lesions after EVT. We identified the volume of the lesion, the affection of grey matter and the plasmatic coagulation system as independent factors for the development of such lesions.
EVALuna2:536989